Construction and Identification of New Molecular Markers of Triple-Negative Breast Cancer Stem Cells - Liu, Tingting; Wang, Hongyue; Liu, Zhiyong; Zhang, Jing; Liu, Yan; Zhang, Lin; Zheng, Chunhui; Liu, Fei; Hou, Chuanqiang; Li, Baojiang (Frontiers in Oncology, 2021)
Objective: We screened the TNBC stem cells using phage display (PD) and acquired the specific binding clones; and then the positive phage DNAs were amplified and extracted, synthesized with specific polypeptides, and labeled with fluorescein isothiocyanate (FITC). Finally, we identified the specificity of the polypeptides in vitro and in vivo. Methods: Human breast cancer cell line MDA-MB-231 and human mammary gland cell line hs578bst were chosen in our study, and MDA-MB-231 breast cancer stem cells (BCSCs) were cultured and identified by flow cytometry. The phage peptide library was screened using MDA-MB-231 BCSCs, the positive phage clones were identified by ELISA, and the DNA of the positive phages was extracted and sent to a biotechnology company for sequencing. According to the sequencing results, a specific polypeptide was synthesized and labeled with FITC. In the end, the specificity of a polypeptide to BCSCs was identified in vivo and in vitro. Results: The MDA-MB-231 BCSCs were cultured and enriched with the “serum and serum-free alternate” method. The BCSCs were found to have characteristics of CD44+/CD24−/low epithelial surface antigen (ESA) and ALDH+ with flow cytometry. The phage was enriched to 200-fold after three rounds of screening for MDA-MB-231 BCSCs. The positive phages were sequenced; then a polypeptide named M58 was synthesized according to sequencing results. Polypeptide M58 has a specific affinity to MDA-MB-231 BCSCs in vivo and in vitro. Conclusion: Specific polypeptides binding to MDA-MB-231 BCSCs were screened out by PD screening method, which laid a theoretical foundation for the targeted therapy and further research of BCSCs.